Contradictions and convergences in recommendations on physical activity in pregnancy in different countries after the publication of the WHO guidelines in 2020—a scoping review - Worska, Aneta; Maciaszek, Janusz; Ciążyńska, Julia; Szumilewicz, Anna (Frontiers in Public Health, 2025)
ObjectivesThe main objective of this review is to determine whether the physical activity (PA) recommendations during pregnancy issued by public health and sports medicine organizations published since 2020 in different countries around the world converge or differ and what are the emerging trends in these guidelines.MethodsThe review was conducted as per the PRISMA Extension for Scoping Reviews (PRISMA-ScR). We searched scientific databases (PubMed, ScienceDirect, Web of Science, Academic Search Complete, and SPORTDiscus with Full Text via EBSCO) and the Internet to identify papers regarding official recommendations on PA during pregnancy published by public health and sports medicine organizations. We analyzed 10 eligible guidelines, published from 2020 in English from eight countries and two international organizations.ResultsThe analysis of the guidelines revealed that all of them advocate for moderate-intensity PA during pregnancy. Seven documents recommended also vigorous or high-intensity activities. Some guidelines recommend it only after consultation with a healthcare provider, particularly for participants with specific health conditions. The analysis of the guidelines shows a convergence on the frequency and duration of PA, suggesting at least 150 min per week.ConclusionThere is a general convergence around the safety and benefits of moderate-intensity PA during pregnancy. There is a divergence in recommendations regarding higher-intensity exercise and altitude training, with limited specific guidance for these activities. However, we have seen much greater openness in this area over recent years. Our work highlights a knowledge gap regarding the safety and efficacy of more intense exercise regimens for pregnant women, emphasizing the need for further research to develop evidence-based guidelines and to address new trends in pregnant population.Systematic review registrationThe study protocol was registered on Open Science Framework (registration number: 10.17605/OSF.IO/3QFR9).